Tailoring nanostructured Ni-Nb metallic glassy thin films by substrate temperature. (1st August 2020) - Yao, W.; Cao, Q.P.; Liu, S.Y.; Wang, X.D.; Fecht, H.J.; Caron, A.; Zhang, D.X.; Jiang, J.Z.
Abstract: Improving the thermostability and mechanical properties of metastable amorphous materials are critical for their potential applications. Here we report the achievement of a wide variety of nanostructures and properties in Ni-Nb metallic glass thin films (MGTFs) by tuning the substrate temperature ( Tsub ) during magnetron sputtering. By gradually increasing Tsub close to glass transition temperature ( Tg ) from room temperature, we evidence the transition from the hierarchical nanostructure with microcracks to the denser nanostructure with a smoother surface and smaller column/particle size. This transition contributes to the enhanced plastic deformation stability and nanomechanical properties, thermal stability, and optical reflectivity in the visible light wavelength. We explain the nanostructure evolution with Tsub based on the competition between the shadowing effect and surface diffusion. The shadowing effect is dominant in low- Tsub films and promotes the voided boundaries, while surface diffusion is remarkably enhanced at high Tsub (0.76–0.87 Tg ) to form dense intergrain boundaries. This finding provides a promising avenue towards producing novel functional MGTFs with controllable nanostructures and properties without any post-treatment. Graphical abstract: Image, graphical abstract